Positron emission tomography derived metrics in relapsed or refractory large B‐cell lymphoma with residual disease before autologous stem cell transplant. (6th September 2022) - Cherng, Hua‐Jay J.; Xu, Guofan; Feng, Lei; Steiner, Raphael; Fayad, Luis; Strati, Paolo; Nair, Ranjit; Nastoupil, Loretta J.; Lee, Hun Ju; Neelapu, Sattva S.; Flowers, Christopher R.; Rodriguez, Maria; et al.
Summary: Salvage chemotherapy followed by high‐dose chemotherapy and autologous stem cell transplantation (ASCT) is a potentially curative treatment for patients with relapsed or refractory large B‐cell lymphoma (rrLBCL) with chemosensitive disease. A 18 F‐fluorodeoxyglucose positron emission tomography (PET) scan after salvage chemotherapy is used to assess response and eligibility for ASCT, but metrics for chemosensitivity in patients with residual disease are not well defined. We performed a single‐centre retrospective analysis of 92 patients with a partial response or stable disease after salvage chemotherapy for rrLBCL who received ASCT to investigate PET‐derived parameters and their prognostic utility. The Deauville 5‐point Scale (D‐5PS) score, maximum standardised uptake value (SUVmax ), total metabolic tumour volume (TMTV), and total lesion glycolysis (TLG) were calculated from the post‐salvage/pre‐ASCT PET scan. The 5‐year progression‐free survival (PFS) and overall survival (OS) rates were 40% and 54% respectively. A D‐5PS score of 5 ( p = 0.0082, hazard ratio [HR] 2.09), high SUVmax ( p = 0.0015, HR 2.48), TMTV ( p = 0.035, HR 1.83) and TLG ( p = 0.0036, HR 2.27) were associated with inferior PFS. A D‐5PS score of 5 ( p = 0.030, HR 1.98) and high SUVmax ( p = 0.0025, HR 2.55) were associated with inferior OS. PET‐derived parameters may help prognosticate outcomes after ASCT in patients with rrLBCL with residual disease after salvage chemotherapy.